Model'nye pokazateli variabel'nosti serdecnogo ritma begunov na srednie distancii - Cherkashina, E. V.; Petrova, A. Y.; Savvinova, Y. I. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article presents the developed model values of heart rate variability indicators recorded at rest and after standard test load among the athletes of various qualifications, specializing in the long-distance running. These models are based on the significant indicators of the heart rate variability characterized by a high correlation relationship with the indicators of physical fitness of runners in middle distances (r = 0,721-0,893). Models were calculated taking into account the sports specialization and qualifications of the runners. The application of the developed models makes it possible to increase the efficiency of operational and current control aimed at determining and evaluating the functional state of athletes in athletics with the aim of promptly correcting the training process and predicting sports results.